DAMPAK PERUBAHAN BUDAYA KABUPATEN WAKATOBI TERHADAP PEMBELAJARAN DI SEKOLAH DASAR - Haliadi; La Salim; Fikram Hermansyah (CV. Adiba Aisha Amira, 2026)
Cultural transformation is an inevitable social phenomenon, including in Wakatobi Regency, which is experiencing cultural evolution due to the tourism sector, globalization, and the development of information technology. This study aims to examine the impact of cultural changes in the Wakatobi community on the educational process in elementary schools, particularly in the formation of students' character, learning attitudes, and local values. The main problem raised in this study is the shift in local cultural values ​​that influences student behavior and teachers' teaching approaches at the elementary level. The method used in this study is a qualitative approach with a descriptive research type. Data were obtained through observation, in-depth interviews with teachers and principals, and analysis of curriculum documentation and school activities. The data analysis process was carried out through data reduction, data presentation, and thematic drawing of conclusions. The research findings indicate that cultural transformation has resulted in a decrease in the use of regional languages, changes in social interaction patterns among students, and a decrease in the integration of local cultural values ​​into learning. However, cultural change also creates opportunities for innovation in teaching methods based on local wisdom that is relevant and contextual to students' lives. Therefore, flexible pedagogical strategies are needed to positively utilize cultural change in the educational process in elementary schools.